Relationships between the Older Adult’s Cognitive Decline and Quality of Life: The Mediating Role of the Assistive Mobile Health Applications - Ali Saare, Murtaja; Hussain, Azham; Seng Yue, Wong (International Journal of Interactive Mobile Technologies (iJIM), 2019)
This article examines the link between the older adult’s cognitive decline, and Assistive Mobile Health Applications in terms of quality of life as researcher has found scarcity in explaining the mediating role of assistive mobile health applications towards the quality of life of older adults with cognitive decline. Researchers have identified the importance of using assistive mobile health applications in connection of the older adult’s cognitive decline. However, it remained unaddressed in the explaining the mediating role of assistive mobile health application. Therefore, this paper aims to provide an insight that the adoption of assistive m-health applications will provide this population with potential solution to their challenging aging life, hence, enhancing their quality of life. In addition, this paper is only a conceptual explanation, as it aims to identify the possible reasons that influence their Smartphone adoption. Factors were identified using a systematic literature review on relevant peer reviewed papers. The study summarized the empirical evidences which were used to support the conceptual explanation. It is expected that this work will lead towards the empirical findings on the explanation of the mediating role of the assistive mobile health applications to address the relationship of older adult’s cognitive decline and quality of life. This paper providesdirections for future studies in improving the quality of life of older adults.